Aqueous production of spherical Zr-MOF beads via continuous-flow spray-drying. Issue 4 (25th January 2018) - Avci-Camur, Ceren; Troyano, Javier; Pérez-Carvajal, Javier; Legrand, Alexandre; Farrusseng, David; Imaz, Inhar; Maspoch, Daniel
Abstract : Water is used in the spray-drying technique to synthesise microsized spherical beads of two Zr-MOFs. Abstract : Porous metal–organic frameworks (MOFs) are attracting great attention from industry, thanks to their myriad potential applications in areas such as catalysis and gas storage. Zr-MOFs (also known as UiO-type MOFs) are especially promising, owing to their large surface areas, high chemical versatility and remarkable hydrothermal, chemical and thermal stabilities. However, among the challenges currently precluding the industrial exploitation of MOFs is the lack of green methods for their synthesis. Herein we describe a continuous-flow spray-drying method for the simultaneous synthesis and shaping of spherical MOF microbeads in a mixture of water and acetic acid. We used this approach to build two archetypical Zr-MOFs: UiO-66-NH2 and Zr-fumarate. By tuning the concentration of acetic acid in water, we were able to produce, by a scalable process, UiO-66-NH2 and Zr-fumarate beads with S BET and water-sorption values comparable to the literature values obtained with other methods.